Asset Administration Shell pro operátora - Houdek, Vojtěch (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2022)
Tato bakalářská práce se zabývá tématem AAS (asset Administration shell), tedy prvkem průmyslu 4.0. První polovina práce je tvořena teoretickým rozborem pojmu AAS a jeho aktivní a pasivní částí. Druhá polovina je věnována praktickému navrhu a implementace AAS pro operátora. Je zde řešena implementace komunikační architektury a volba vhodného Hardwaru pro AAS. Výsledná realizace se zabývá programováním aktivní a pasivní částí AAS v C/C++ a mobilní aplikací v Android Studiu za pomocí programovacího jazyka Kotlin.

This bachelor thesis deals with the topic of AAS (asset administration shell), an element of industry 4.0. The first half of the work consists of a theoretical analysis of the concept of AAS and its active and passive parts. The second half is devoted to the practical design and implementation of AAS for the operator. The implementation of the communication architecture and the selection of suitable Hardware for AAS are addressed here. The resulting implementation deals with programming the active and passive part of AAS in C/C ++ and mobile applications in Android Studio using the programming language Kotlin
Asset Administration Shell for the operator
Keywords: AAS; Průmysl 4.0; pasivní část AAS; aktivní část AAS; OPC UA; C++; Kotlin; Android.; AAS; Industry 4.0; passive part of AAS; active part of AAS; OPC UA; C++; Kotlin; Android